TINJAUAN ASAS KERAHASIAAN DALAM PERLINDUNGAN DATA PRIBADI NASABAH BANK DIGITAL PADA HUKUM POSITIF INDONESIA - Ifana Marsha Bella; Umi Khaerah Pati (Fakultas Hukum Universitas Sebelas Maret, 2026)
This article examines the adoption of the principle of confidentiality in the protection of personal data of digital bank customers on positive law in Indonesia. This research is a prescriptive normative with statutory approach. The data used were primary data, secondary data, and tertiary data. Data collection techniques carried out by literature study or document study with deductive syllogism legal material analysis techniques. The results of the research and discussion show that the adoption of the principle of confidentiality in terms of the protection of personal data for digital bank customers can be found in several laws and regulations in Indonesia. Starting from the level of law, government regulation, ministerial regulation, financial services authority regulation, bank Indonesia regulation, and circular letter. The basic provisions of confidentiality stipulated in these regulations are still general in nature and only cover certain matters. Among them are the definition of bank secrets, bank confidential exceptions, the right of customers to get personal data protection, the obligation of digital banks to provide protection of personal data, and certain prohibitions that can harm customers.